Recent Progress in Multifunctional Graphene Aerogels - Kotal, Moumita; Kim, Jaehwan; Oh, Junghwan; Oh, Il-Kwon (Frontiers in Materials, 2016)
Two dimensional (2D) graphene has become one of the most intensively explored carbon allotropes in materials science owing to attractive features like its outstanding physicochemical properties. In order to further realize practical applications, the fabrication of self-assembled 2D individual graphene sheets into 3D graphene aerogels (GAs) with special structures and novel functions, is now becoming essential. Moreover, GAs are ideal as supports for the introduction of nanoparticles, polymers, and functional materials to further enhance their applications in broad areas. GAs have light weight, large surface area, good compressibility, extensibility, and high electrical conductivity. They have been used as efficient electrodes for batteries, in supercapacitors, and in sensors and actuators. This critical review mainly addresses recent progress in the methods used for their syntheses, their properties, and applications for energy storage, and in sensors and actuators. Furthermore, to assist advanced research for practical applications of these emerging materials, the technical challenges are discussed, and future research directions are proposed.